STRENGTHENING STUDENTS’ CHARACTER THROUGH THE INTEGRATION OF NIAS LOCAL WISDOM IN PANCASILA AND CIVIC EDUCATION - Darmawan Harefa (Universitas Nias Raya, 2026)
This study examines the strengthening of students’ character through the integration of Nias local wisdom in Pancasila and Civic Education (PPKn) at senior high schools in South Nias. The research aims to analyze how local cultural values can be incorporated into civic learning to enhance students’ moral development, civic awareness, and cultural identity. A qualitative descriptive approach was employed using interviews, classroom observations, and document analysis involving teachers and students. The findings reveal that integrating Nias local wisdom, such as communal values, mutual cooperation, and customary law, significantly improves students’ character traits, including responsibility, discipline, honesty, and respect. Students also demonstrate higher engagement, motivation, and participation during learning activities when lessons are contextualized with their cultural environment. Furthermore, the integration of local wisdom helps students better understand civic concepts by linking them to real-life experiences. This approach not only strengthens cognitive understanding but also fosters affective and behavioral development in line with Pancasila values. However, challenges such as limited learning resources and lack of structured teaching materials were identified. Despite these limitations, the study concludes that the integration of Nias local wisdom in PPKn is an effective strategy for character education and cultural preservation. Therefore, it is recommended that schools and policymakers support the systematic incorporation of local wisdom into the curriculum to ensure sustainable character development among students.